Analysis of the Implementation of Minimum Service Standards (SPM) on the Minimum Service Quality of Hospitals: A Case Study at Mentawai Islands Regional Hospital, West Sumatera, Indonesia - Fadlika, Avissa; Rizanda Machmud; Abdi Setya (HM Publisher, 2024)
Minimum service standards (SPM) are an important instrument in ensuring the quality of health services in hospitals. This research aims to analyze the implementation of SPM on minimum service quality at the Mentawai Islands Regional Hospital, West Sumatera, Indonesia. This research uses a mixed-method design with a sequential explanatory approach. The quantitative phase involved collecting secondary data from medical records and patient satisfaction surveys (n=300). Logistic regression analysis is used to identify the relationship between SPM implementation and service quality. The qualitative stage involved in-depth interviews with hospital management (n=5) and health workers (n=10) to explore factors influencing SPM implementation. The results of the quantitative analysis show that the implementation of SPM is significantly associated with an increase in minimum service quality, especially in the aspects of patient safety, clinical effectiveness and patient experience. Qualitative interviews revealed that factors such as resource availability, management commitment, and staff training influence the success of SPM implementation. Effective implementation of SPM contributes to improving the minimum service quality at the Mentawai Islands Regional Hospital. To optimize the implementation of SPM, increasing the availability of resources, strengthening management commitment and ongoing training programs for staff is needed.